A one health perspective on a recent outbreak of monkeypox - Hill, Katherine (Kansas State University, 2023)
The monkeypox virus, or mpox virus, is a highly communicable orthopoxvirus that was first observed in the mid-twentieth century. The virus causes monkeypox, a zoonotic disease characterized by pox lesions and swollen lymph nodes. While mpox is endemic in parts of Africa, it is not typically seen outside the continent. It was recently detected in the United States in May 2022, with rapid escalation in cases both domestically and internationally. The outbreak was declared an international public health emergency in July 2022 and a domestic public health emergency the following month. Since the transmission of this zoonotic disease can be impacted by humans, animals, and the environment, a One Health approach to surveillance, treatment, prevention, and education is imperative for public health. More specifically, a successful One Health approach to any zoonotic disease outbreak must incorporate human, animal, and environmental health experts. Depending on the nature of the disease, the focus may initially be on one aspect of this triad. In the case of the recent outbreak, the emphasis was primarily on human health when only a small number of cases were reported. As the caseload grew from single digits to hundreds of new cases diagnosed daily, it became apparent that extensive human health investigations should include veterinary, environmental, wildlife, and public policy assessments. The purpose of this report was to discuss and apply a One Health approach in retrospect to address and mitigate the impact of the 2022 monkeypox outbreak in the United States.
Keywords: Monkeypox; Mpox; One health